Irritable bowel syndrome with constipation: issues of pathogenesis, diagnostics and treatment - Grydnieva, Svitlana; Reznichenko Olexandr; Martynenko, Maksym; Гріднєва, Світлана Вікторівна; Резніченко, Олександр Георгійович; Мартиненко, Максим Вікторович (Харків : Харківський національний університет імені В.Н. Каразіна, 2020)
Issues related to the diagnosis and treatment of irritable bowel syndrome occupy one of the central places in gastroenterology, due to the fact that in recent years there has been a significant increase in the incidence of this syndrome, its long-term recurrent, often lifelong course, leading to a decrease in the performance of patients, despite good quality, and a significant cost to the health care system. Irritable bowel syndrome, despite its functional nature, occurs quite often - from 14-50% of the adult population according to population epidemiological studies, and the ratio of women to men is from 2: 1 to 4:1. In the structure of gastroenterological pathology, this disease accounts for 40 -70% of all cases of seeking medical help. Irritable bowel syndrome is a complex of functional disorders of the distal intestines, lasting more than 3 months and accompanied by abdominal pain that disappears after a bowel movement, flatulence, a feeling of incomplete bowel movement, changes in the frequency and consistency of stools. Factors in the pathogenesis of irritable bowel syndrome are dysfunction of mental activity with changes in autonomic and humoral functions; visceral hypersensitivity and impaired intestinal motility, past intestinal infection; endocrine disorders; food allergies, sedentary lifestyle; gen etic predisposition. Endothelial dysfunction has recently played an important role in the onset of irritable bowel syndrome. The most famous among the factors of vascular endothelium today are the powerful vasoconstrictor endothelin-1 and the vasodilator - nitric oxide. The study investigated the level of vasoconstrictor endothelin-1 and vasodilator of nitric oxide in patients with irritable bowel syndrome with constipation. It was found that such patients have severe endothelial dysfunction, which manifest s itself in an increase in the level of endothelin-1 (р˂0,01), a decrease in the level of nitric oxide (р˂0,01). The data obtained indicate the role of dysfunction of the vascular endothelium in the pathogenesis of irritable bowel syndrome with constipation. An inverse correlation was found between the content of endothelin -1 and nitric oxide (p˂0.01), which indicates an increase in the activity of vasoconstrictor mechanisms with a simultaneous decrease in vasodilation factors. The effectiveness of complex therapy in the group of patients in whom folic acid and zincteral were used as part of complex therapy in improving the clinical picture of the disease (complete relief of dyspeptic syndrome and a significant decrease in the severity of pain, constipation and asthenic syndromes), restoration of vascular endothelial function (significant decrease in the level of endothelin-1 and an increase in the level of nitric oxide) in comparison with the group of patients in the treatment of which only basic therapy was used.
Наукова стаття
Keywords: MEDICINE::Dermatology and venerology,clinical genetics, internal medicine::Internal medicine::Gastroenterology; irritable bowel syndrome; onstipation, endothelin -1; nitric oxide; endothelial dysfunction